Maritime English - Teaching Competencies in Facilitating Difficulties with Students - Celo, Evis; DANAJ, Lorenc; CELO, Jonil (European Journal of Multidisciplinary Studies, 2016)
Recognizing ship operating which differ in their organizing way helps in prevention of human injuries ;loss of life and avoidance of damage to the environment,in particular to the maritime environment and its property. The main aim is developing English for Maritime and having the right communication in different, specific and also in dangerous situation at sea. This paper consist on recognizing deeply the IMO standard on sea level including the IMO convention; SOLAS convention, MARPOL as well as STCW certificate and code too. So, advancing knowledge, understanding properly the right message at the sea including proficiency in having adequate knowledge of English language in order to enable officers - new students to communicate with other ships - coast stations to perform the officers duties. A great importance is based on cooperation of standard Marine Communication Phrases and use of International English both in written and oral form.. Not only that,but also multilingual communication crew, including abilities to use the IMO standard with Marine Communication Phrases! Difficulties and progresses are evident, but the necessity and the particular availability of Modern and Post Modern time let upon us this task open